The impact of teacher-student interactions on student engagement and satisfaction in blended learning environments: An exploratory study using multi-source data - Xu, Yutao; Baharom, Sadiah (Journal of Education and e-Learning Research, 2026)
Existing literature on blended learning in higher education predominantly relies on student surveys, offering a limited perspective on actual classroom dynamics. To address this gap, this study examines the mutual influence among teacher-student interaction, student engagement, and satisfaction within blended learning environments at a Chinese university. A mixed-methods approach was adopted, integrating three data sources: classroom observations, student perception surveys, and behavioral data from the Learning Management System (LMS), using a triangulation design to comprehensively explore the relationship between interaction quality and learning. The findings reveal that personalized feedback, especially the emotional support provided by teachers, is crucial for student satisfaction. While LMS data clearly reflect certain aspects of behavioral engagement, they show little correlation with students’ affective engagement or perceived instructor support. Importantly, affective support not only strongly predicts student satisfaction but also appears to compensate for lower levels of online activity. These results suggest that in blended learning contexts, emotional and personalized interaction from instructors plays a vital role in fostering satisfaction, potentially outweighing the influence of online activity metrics. In practice, institutions and instructors should prioritize meaningful interpersonal engagement and affective feedback, rather than relying primarily on digital activity indicators, to enhance students' learning experiences and outcomes.